IBADAH RUMAH, ANAK DAN COVID-19 - Marlen Alakaman (IAKN Ambon, 2021)
Worship is a part of a people's response to God's love and grace. The home and the church become a family as the church that allows fellowship to be established in building faith and trust to the response of God's love and creation for humans and Christian teaching is carried out. Since the Covid-19 pandemic, church activities and related services must be carried out in other forms, namely by doing worship in their home and it was guided by a liturgy that has been prepared and provided by the Synod and Klasis. Worship at home by involving children who have a different character and spiritual growth based on their era. Menconi in his efforts towards an intergenerational church gave an area of service in the church, namely: Intergenerational worship which then became the writer's scalpel in analyzing research data and described qualitatively. The results of this research become a reference when the church implements worship at home during a pandemic, so the family is called the center of early education for a child and by worshiping at home, it can be said that there is a division of roles in worship together within the family. All of the families s in turn are given roles and functions to carry out the duties and responsibilities of the service. It has a positive impact where family fellowship is used as the initial basis for growth and development in ministry. The Children will understand about worship is an inseparable part of the reality of life and the challenges faced during a pandemic. This is a concern and the role of the church as an institution to assist the government in overcoming the COVID-19 pandemic by reducing the number of people exposed or dying, and the church as a community remains awake and it does not eliminate the meaning of worship itself by worshiping at home.